Research on residents' (re)mediation and dismissal in the interest of society - Judith Godschalx-Dekker; Walther van Mook (Societal Impacts, 2025)
This article presents key findings from a Dutch nationwide research project on law cases in postgraduate medical education (PGME). Within the project, ten years of law cases on residents’ dismissal from training programs in medical specialties were reviewed. The findings provided opportunities for improving the quality of residents’ assessment, remediation, and dismissal procedures. Case examples of dismissal procedures demonstrated the potential of 'learning from law cases', whether these cases were typical or exceptional. Unexpected and unfavourable outcomes after (re)mediation in PGME provided additional examples to learn from, and contributed to the continuous professional education of clinical supervisors and hospital education staff. The project’s primary outcome is that it explicates the often implicit expectations about the functioning of future medical specialists and, secondarily, that it creates awareness about changes required to improve the quality and inclusivity of PGME. Apart from its relevance for PGME, the increased awareness on these topics may ultimately benefit society because residents as highly educated healthcare professionals are future role models within a hospital’s hierarchy. Such societal impact is generated by multi-stakeholder collaboration in workshops and publications, enhancing critical reflection on the quality of and safety culture in PGME.